Hierarchical Porous Carbon with Nano-MgO as Efficient Sulfur Species Micro-Reactors for Lithium-Sulfur Battery. Issue 4 (1st April 2021) - Zhao, Xiangyang; Wang, Jiayu; Sun, Xiaogang; Wei, Kunrui; Wang, Weikun; Wang, Anbang; Huang, Yaqin; Guan, Yuepeng
Abstract : The rechargeable lithium-sulfur (Li-S) battery has been considered as one of the most ideal energy storage systems on account of its high energy density and low cost. However, the inevitable shuttle effect of polysulfides (LiPSs) seriously restrains its commercial application. Here, nano-MgO with crab shell-based hierarchical porous carbon composites (nano-MgO@CSHPC) have been successfully prepared and employed as effective sulfur species micro-reactors for the Li-S battery. The hierarchical micro/mesoporous structure of CSHPC can provide enough area to physically restrict the LiPSs migration and accommodate the volume expansion. Besides, the nano-MgO formed in the carbon pore can chemically anchor the LiPSs and minimize LiPSs dissolution. Moreover, the nitrogen in the CSHPC can availably enhance LiPSs restriction and improve the conductivity of carbon network. Our work reveals that the rational design of sulfur species micro-reactor simultaneously achieves LiPSs immobilization and conversion, which is helpful to promote the practical application of Li-S battery.